If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 1) + -9(x + 1) = 0 Reorder the terms: x(1 + x) + -9(x + 1) = 0 (1 * x + x * x) + -9(x + 1) = 0 (1x + x2) + -9(x + 1) = 0 Reorder the terms: 1x + x2 + -9(1 + x) = 0 1x + x2 + (1 * -9 + x * -9) = 0 1x + x2 + (-9 + -9x) = 0 Reorder the terms: -9 + 1x + -9x + x2 = 0 Combine like terms: 1x + -9x = -8x -9 + -8x + x2 = 0 Solving -9 + -8x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-1 + -1x)(9 + -1x) = 0Subproblem 1
Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1Subproblem 2
Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9Solution
x = {-1, 9}
| -3(3-5y)=10y+41 | | 11(11x-2)=5 | | 5z-3=5+4z | | -13-7x=-6-9(x+3) | | A=a+(n+1)d | | -17+8=-3(x+2) | | x(x+3)-6(x+3)= | | 6x+7=-3 | | 3p-(p-5)=2(p+4) | | A=a+(n-1)d | | 4x+2=8x+22 | | 4x^3(x-2)-2x(x-2)= | | -8(x+9)=-7x-3 | | 4(6t+5)+9t+3(4t+7)= | | 2x+7y=21 | | -18+-6= | | 3x-6=5-2x | | 9(-2)= | | 1+7(4+3t)+5(12+t)= | | 3(2+5x)-10=-22+6x | | 2(5t+8)+9(2t+1)= | | 9y-6= | | 4=s/5-16 | | 10=6+t/8 | | 7+2(3+n)+11n= | | t/6+12=24 | | 16(n+1)+4n+6(5+n)= | | 3x-10y=25 | | (x^2)-(x+2)(x+2)=-3(x-2) | | s/3-7=7 | | n+4(n+9)+20= | | 9+r/5=15 |